External Adjustment and the Strong Yen : Recent Japanese Experience. (IMF Working Papers; Working Paper ;, 1988)
The parameters of a conventional model of Japan's current account were found to be stable in the period of the steeply rising yen between the fourth quarter of 1985 and the end of 1987. This suggests that Japan's current account has been adjusting to the strengthening yen in accordance with established historical relationships-a conclusion that is substantiated by the model's reasonably accurate tracking of the current account in this period. Furthermore, simulations of the model show that the rise in the yen has already made a substantial contribution to correcting Japan's external imbalance.